Electricity and magnetism - Crane, Cody (New York : Children's Press, an imprint of Scholastic, Inc., 2019)
"This book details the science of electricity and magnetism. It explains how these forces work, how they are related, what uses people have found for them, and more."--
It's electrifying! -- Electric currents -- Magical magnetism -- Useful tools.
Includes bibliographical references and index.
Keywords: Electricity -- Juvenile literature; Magnetism -- Juvenile literature